Analysis Of The Use Of The Wattpad Application As A Media For Developing Creativity Of Islamic Broadcast Communication Students For The Lifting Of 2017 - Farah Divta Nastassyah; Suryati Suryati; Hasril Atieq Pohan (Program Studi Komunikasi dan Penyiaran Islam UIN Raden Fatah Palembang, 2023)
The background to the problem of this research is that there are many applications similar to Wattpad that can be used as a medium to develop creativity, especially among Islamic broadcasting communication students class of 2017, such as Webtoon or Mangatoon. The aim of the first research is to determine the analysis of the use of the Wattpad application as a medium for developing creativity for Islamic Broadcasting Communication students, Class of 2017. The research uses qualitative methods. Data collection techniques through observation, questionnaires and documentation. The results of the research show that there is an analysis of the use of the Wattpad application as a media for developing the creativity of Islamic Broadcasting Communication Students Class of 2017, namely to convey the content of a story or prepare a final college assignment report, remembering that students in the final semester are busy and they can use the Wattpad application to make it easier. for all their work, this application is an opportunity for them to share stories both in terms of cognition, affection and connotation that can convey students' feelings in any situation.